Fournier's Gangrene due to Masturbation in an Otherwise Healthy Male. (22nd May 2012) - Heiner, Jason D.; Eng, Katisha D.; Bialowas, Todd A.; Devita, Diane
Abstract : Fournier's gangrene is a rare and often fulminant necrotizing fasciitis of the perineum and genital region frequently due to a synergistic polymicrobial infection. This truly emergent condition is typically seen in elderly, diabetic, or otherwise immune-compromised individuals. Here, we report an unusual case of Fournier's gangrene due to excessive masturbation in an otherwise healthy 29-year-old male who presented to the emergency department complaining of two days of fever, vomiting, and diffuse myalgias. Upon further questioning, he also endorsed severe scrotal pain and swelling and frequent masturbation with soap as a lubricant resulting in recurrent penile erythema and minor skin abrasions. Examination of the patient's perineum was consistent with Fournier's gangrene and included significant erythema, edema, and calor of the penis and scrotum with a large malodorous eschar. He was given intravenous antibiotics and immunoglobulin and promptly underwent three surgical debridements of the scrotum and penis with split-thickness skin grafting. Complications from excessive masturbation are exceedingly rare, but as this case illustrates, they can be life threatening.